Efficiency assessment of knowledge intensive business services industry in Italy: data envelopment analysis (DEA) and financial ratio analysis. Issue 4 (20th November 2019) - Campisi, Domenico; Mancuso, Paolo; Mastrodonato, Stefano Luigi; Morea, Donato
Abstract : Purpose: Within the service sectors, Knowledge Intensive Business Services (KIBS) play an important role in local and regional economies as sources of competitive advantages and providing knowledge-intensive inputs to the business process of small and medium-sized enterprises. This study aims to analyze the changes in financial performance of KIBS industry in Italy over the period from 2012 to 2017. Design/methodology/approach: This paper examines the efficiency of the KIBS firms by applying data envelopment analysis (DEA) to compute the Malmquist Productivity Index for the period under investigation. The DEA-based Malmquist productivity analysis is applied at firm level using a sample consisting 1.674 companies, representative of the Italian KIBS sector and related to three different NACE activity code (72-computing services; 73-research and development; 74 other professional business activities). The efficiency measures are then used to characterize KIBS firm financial performance through the analysis of average productivity patterns grouped by Italian geographical regions. The Malmquist productivity measures are decomposed into two components: efficiency change and technical change index. The overall analysis is coupled with a financial ratio analysis approach, selecting return on equity (ROE) and leverage ratio as descriptor to validate the results and better characterize differences in efficiency patterns among geographic-based groups of KIBS companies. Findings: Over the period 2015-2017, the results show that the average annual growth of the overall Malmquist productivity index was positive in nine Italian regions that represent only 17 per cent of the total KIBS firms selected. On the other side, a decrease of the average performance measure is observed for the five geographic areas that contribute to 75.7 per cent of the total sample. In general, the technological change component, as a measure of innovation, strongly limits the productivity growth behavior of KIBS industry for all geographic regions. The use of selected financial ratio does not provide additional insight to the performance investigation and further in-depth studies are needed to better evaluate the correlation between average productivity results and regional business dynamics. Practical implications: The study investigates the applicability of DEA-based Malmquist indices to the analysis of the productivity behavior of KIBS industry at regional level. It will be of value to provide first evidence to the policymakers to understand industry growth pattern in time frame selected and relate them to additional business factors to detect specific industry constraints. Originality/value: The analysis in this paper contributes to the existing body of knowledge on industry performance measurement by applying specific analytical techniques to the productivity of Italian KIBS companies. The paper also contributes to the limited body of academic literature investigating KIBS industry at national level proposing a methodological framework that constitutes a first attempt to track average productivity behavior at regional level.